Navigation-assisted Excision of Heterotopic Ossification in Bilateral Hips of a Paraplegic Patient: A Case Report with Technical Note - Mirunaalini Thangavelan; Keerthivasan Panneerselvam; Sathish Venugopal; Aravindan Selvaraj; Mukunth Krishnamoorthy; Vikraman Arunachalam (Journal of Orthopedics and Joint Surgery)
Aim and background: Heterotopic ossification (HO), which is common among patients with neurological disorders or chronic bedridden individuals, is a major concern for mobility and rehabilitation. Here, we have discussed a novel technique in the surgical management of HO in a 27-year-old posttraumatic paraplegic patient. Case description: This is the very first case to our knowledge in which excision of HO in bilateral hips was performed with navigation assistance, after which the patient regained full range of joint movement and intensive physiotherapy was possible. Conclusion: Excision of HO in this paraplegic patient with bilateral hip ankylosis and knee stiffness and challenges imposed due to preexisting conditions were surpassed with navigation assistance. Three-dimensional (3D) navigation guidance in HO resection may aid in overcoming the surgical challenges and optimizing the final outcome. Clinical significance: Surgical excision in extensive HO lesions can be a prompt decision for patients, especially in terms of better rehabilitation and prevention of complications. In addition to meticulous preoperative planning, technical guidance with navigation assistance during surgery may serve as a viable option.